Study of endotracheal tube cuff pressure and time of measurement among intensive care units patients - Leila Taslimi; Tahere L1, Khaleghdoost Mohammadi; Atefeh Ghanbari; Ehsan Kazemnezhad Leili (Guilan University of Medical Sciences, 2016)
Introduction: The pressure in the endotracheal tube cuff must be kept within an optimal range, to make sure tracheal capillaries circulation still stable during positive ventilation. This is essential to avoid oral and gastric stuffing aspiration Objective: The objective of this study was to assess the endotracheal tube cuff pressure and time intervals measurements among intensive care units patients Methods: This study was cross sectional designed to perform on 61 patients with oral intubation in the intensive care units, Rasht educational therapeutic centers, during the summer of 2013 for three months. A manometer was used to measure the cuff pressure twice every 6 hours interval. Different variables like age, sex, diagnosis, Body Mass Index and days intubated also were measured. All data obtained were analyzed using descriptive statistics (mean, standard deviation distribution) and inferential statistics (T test, Pearson, ANOVA) Results: This study indicated that the cuff pressure was normal in 16.4% cases at the first step and after 6 hours, cuff pressure adjustment increased by 78.7%. The results show that correlation between days intubated and cuff pressure (in first evaluation P= 0.002, in second evaluation P=0.01) and BMI (in first evaluation P= 0.007, in second evaluation P=0.03 were significant Conclusion: This study showed that despite of 6 hours cuff pressure control, the range of miss regulation was 21.3%. This issue highlights that to prevent complication due to over and under inflation of cuff, a fewer intervals between cuff pressure control is required